Balancing livelihoods and environment: political economy of groundwater irrigation in India - Shah, T.; Rajan, Abhishek; Rai, Gyan P. (Elsevier, 2021)
India’s agricultural economy has undergone profound transformation in the past 50 years with the rapid spread of groundwater irrigation. The tube well revolution has democratized irrigation, made famines history, helped alleviate agrarian poverty and made India food secure. However, the spread of private tube wells has cannibalized canals and tanks. The large-scale withdrawal of groundwater has caused acute groundwater stress in several parts of the country, leading to adverse environmental and sustainability challenges. Unlike the United States, Australia, and Spain, where tube wells are instruments of wealth creation in industrial agriculture, in India groundwater governance pits livelihoods of the poor against environmental protection. This study explores this unique challenge. It discusses several efforts undertaken to effectively manage groundwater such as direct regulation, indirect levers like energy pricing and rationing, and community-based groundwater governance. It emphasizes on the arrival of solar irrigation and its potential to reform the perverse energy-groundwater nexus. The paper stresses on the need to move away from resource development to resource management mode to solve the groundwater challenge.